a) (x-34)x15=0
x-34=0 x15
x-34=0
x=34+0(tìm số bị trừ)
x=34
b) 18x(x-16)=18
(x-16)=18:18
x-16=1
x=1+16(tìm số bị trừ)
x=17
a) x-34=0/15=0
x=0+34=34
b) x-16=18/18=1
x=1+16=17
( x - 34 ) x 15 = 0
( x - 34 ) = 0 x 15
( x - 34 ) = 0
X = 0 + 34 = 34
x = 34
18 x ( x - 16 ) = 18
( x - 16 ) = 18 : 18
( x - 16 ) = 1
x = 16 + 1
x = 17
(x-34)*15=0
suy ra (x-34)=0*15
suy ra x-34=0
suy ra x =0+34
suy ra x= 34
18*(x -16)=18
suy ra(x-16)=18/18
suy ra x-16=1
suy ra x =1+16
suy ra x=17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x =17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
Vào lúc: 2016-06-16 07
Ta có : ( x - 34 ) x 15 = 0
=> ( x - 34 ) = 0 : 15
=> ( x - 34 ) = 0
=> x = 0 + 34 = 34
Vậy x = 34
Ta có: 18 x ( x - 16 ) = 18
=> ( x - 16 ) = 18 : 18
=> ( x - 16 ) = 1
=> x = 16 + 1
Vậy x = 17
( x - 34 ) x 15 = 0
( x - 34 ) = 0 x 15
( x - 34 ) = 0
X = 0 + 34 = 34
x = 34
18 x ( x - 16 ) = 18
( x - 16 ) = 18 : 18
( x - 16 ) = 1
x = 16 + 1
x = 17